"A Divina Luz Que Ilumina As Criações": A Cultura Do Samba Autoral Na Comunidade Samba Da Vela - Augusto, Viviane Viola [UNIFESP] (2018)
This Research Deals With The Organization Of The Samba Da Vela Community, Whose Development Was Carried Out, Above All, By The Ethnographic Register. In The Course Of The Research, We Need To Use Other Media, Interviews And Audiovisual Records. The First Factor Of Analysis Was The Selection Criteria Of The Sambas To Integrate The Community Notebooks And, Consequently, The Factors For The Composer And Other Non-Musicians To Be Considered As Members Of The Community. After Analyzing These Items, A Brief Presentation Of The History Of Samba Da Vela And The Movement Of Samba Communities In São Paulo, We Did A Survey Of The Topics Presented In The Notebooks Of The Last Four Years, With The Objective Of Verifying How The Recurrent Themes Ensure The Criteria Analyzed And The Maintenance Of The Ideals Of The Samba Wheel.